ANALISIS PENGGUNAAN JENIS MP-ASI DAN STATUS KELUARGA TERHADAP STATUS GIZI ANAK USIA 7 – 24 BULAN DI KECAMATAN JAYA BARU KOTA BANDA ACEH - Agus Hendra AL Rahmad (Politeknik Kesehatan Kemenkes Mamuju, 2017)
Children under two years is a period with rapid growth and development in (the golden period) and is classified in the group were extremely malnutrition. Complementary feeding and the nutritional status of children cause problems in the aspect of a causal relationship, that the giving its less precise impact on malnutrition status. The study aims to measure the difference in the use omplementary feeding type in families with non-civil and civil servants on the nutritional status of children aged 7 – 24 months in the district Jaya Baru Banda Aceh. The research method with quantitative approach through the cross-sectional design, with a variables consist of the use complementary feeding, nutritional status, and family status. Data was collected through interviews and observations taken at 83 randomly selected samples. Analysis data used with statistical a Chi-Square test on CI:95%. The results showed no difference in proportion of nutritional status (p-value= 0,518) between a families from civil servants with not a family of civil servants (p-value > 0,05). Furthermore, the use omplementary feeding type a proportionally shows the difference with p= 0,005 (p-value < 0,05) in the district of Jaya Baru Banda Aceh. The conclusion that the nutritional status of children between the families of civil servants with not civil servants did not show a difference, but in the use of omplementary feeding by proportion and type of family status have significant differences.